The following problems can be solved using only topics and theorems one encounters in the high school (Polynomials, Calculus, Probability/Statistics, Trigonometry, Analytic Geometry, Induction, etc).

(Martin Gardner) There are \( n\) racecars on a circular track. Amongst the \(n\) cars, there is enough gas for one car to make a complete loop around the track. Show that there exists a car that can make a complete loop around the track by pooling gas from every car that it passes.

(USAMO '73) Find all complex solutions to the following system of equations: \[ \begin{aligned} x+y+z & = 3\\ x^2+y^2+z^2 & =3\\ x^3+y^3+z^3 & = 3.\\ \end{aligned} \]

Find all real solutions to the following system of equations: \[ \begin{aligned} x+y+z & = 3\\ x^2 + y^2+z^2 & =3. \\ \end{aligned} \]

(Live Challenge Number Theory 5) Compute the last 3 digits of \( 171^{172} \).

(Britain '87) \( f(x)\) is a polynomial with integer coefficients satisfying \( f(21)=17\), \( f(32)=-247\), and \( f(37)=33\). If there is an integer value \( N\) such that \( f(N)=N+51\), show that \( N=26\).

(Live Challenge Algebra 4) Let \( x\) be a real number such that \( 0.170 < \log_x 2 < 0.171\) and \( 0.270 < \log_x 3 < 0.271\). Determine the integer that is closest in value to \( \log_x 7^{100} \).

(IMO'68) Determine all triangles whose side lengths are consecutive positive integers such that one angle is twice of another angle.

(*) Calvin and Dan play a game of chance. A fair coin is flipped and the sequence of Heads and Tails is recorded. Calvin wins if the sequence \( HHH\) appears first, and Dan wins if the sequence \( TTHH\) appears first. Who has a higher probability of winning?

Part 2 is available here.

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewest## solution 7

Let the sides be a,a+1,a+2 Let the angle opposite side to a be A,opposite to b be a+1,and side opposite to c be a+2 By using cosine rule, cosA=a+5/2a+4,cosB=a+1/2a and cosC=a-3/2a Using cos2x=2cos^2X-1 We get a=4 for A=2C a=1 for A=2B But a cannot be 1 as difference of two sides should be less than the third side Therefore sides are 4,5 and 6Log in to reply

Sorry no solution here, but I do have a question:

Is there any particular place where I can learn to solve problems like these?

Log in to reply

SOLUTION #4Let's define, for convenience, a function \(f(x)\) that shows the last three digits of \(171^x\). We have,

by grinding, \(f(3)=211, f(9)=931, f(27)=491, f(54)=81, f(162)=441, f(171)=571\) and finally \(f(172)=\boxed{641.}\)Log in to reply

sorry, I cannot understand this grinding.

Log in to reply

Explanation:

\(171^3 = 5000211\), so the last three digits of \(171^3\) are \(211\) (\(f(3)=211\)). \(171^9 = (171^3)^3 = 125015825667824393931\), which has the same last three digits as \(211^3 = 9393931\), so \(f(9)=931\). ...etc...

Log in to reply

Log in to reply

Log in to reply

My attempt for SOLUTION #3

Didn't see a similar solution to mine, thought it was worth a share :)

We are given: \[a+b+c=3 \tag{1} \] \[a^{2}+b^{2}+c^{2}=3 \tag{2}\]

From \((1)\), \(c=3-a-b\).

Plugging that into \((2)\) we obtain, \[a^{2}+b^{2}+(3-a-b)^{2} = 3\]

Expanding the brackets and simplifying it we attain, \[a^{2}+ab-3a+b^{2}-3b+3=0\]

It can be rewritten as, \[a^{2} + a(b-3) + (b^{2}-3b+3) = 0\]

Hence, using quadratic formula: \[a = \frac{-(b-3) \pm \sqrt{(b-3)^{2}-4(b^{2}-3b+3)}}{2} \tag{3} \]

The discriminant must be \( \ge 0\) to have real roots so, \[ (b-3)^{2}-4(b^{2}-3b+3) \ge 0 \]

Simplifying the quadratic inequality above we obtain, \[ -3(b-1)^{2} \ge 0 \]

Solving the quadratic inequality we observe that the only solution for b is, \( \boxed{b=1} \).

Hence, solving for \( a\) using \( (3) \) we obtain, \[ a = \frac{-1(1-3) \pm \sqrt{-3(1-1)^{2}}}{2} =\frac{2}{2} \]

\[ \boxed{a=1} \]

Therefore, \(c\) can be easily calculated using equation \( (1)\), \[ c = 3 - 1 -1 = 1 \]

The only

realsolution to this question is:## \[ \boxed{ (a,b,c) = (1,1,1) } \]

Log in to reply

Nice. Is there an easier way to get at this?

Log in to reply

\(a+b+c=3\\ { a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }=3\\ which\quad implies,{ a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }-ab-bc-ca=0\\ =>\frac { 1 }{ 2 } (({ a }^{ 2 }-2ab+{ b }^{ 2 })+({ a }^{ 2 }-2ac+{ c }^{ 2 })+({ b }^{ 2 }-2bc+{ c }^{ 2 }))=0\\ =>{ (a-b) }^{ 2 }+{ (b-c) }^{ 2 }+{ (a-c) }^{ 2 }=0\\ =>a=b=c=1\)

Log in to reply

Log in to reply

Log in to reply

Log in to reply

An easier way, as requested:

Let \(x+y+z=3\). We have that \(3(x^2+y^2+z^2)\ge (x+y+z)^2\) by Cauchy. Dividing by \(3\) on both sides, we have \(x^2+y^2+z^2\ge x+y+z\), where equality case is \(x=y=z\). However, since \(x^2+y^2+z^2=x+y+z\), then we must have \(x=y=z\). Solving with this condition in mind easily gives us \(x=y=z=1\) as the only solution.

Log in to reply

Log in to reply

Log in to reply

The other approach is to think of the geometric interpretation. We have a plane and a sphere, which intersect at the obvious point \( (1, 1, 1) \). To show that this is the unique point of intersection, it suffices to show that the plane is tangential to the sphere.

Log in to reply

Log in to reply

If you are familiar with 3-d vectors, then you find the vector that is perpendicular to the plane, and show that is is parallel to the vector perpendicular to the sphere at the point of contact.

If you are familiar with multivariable calculus, you just apply the definition of tangency, which is a restatement of the above.

If you are familiar only with 2-d concepts, then take any plane and show that the intersection with this plane produces a circle and a line which are tangential.

Log in to reply

Log in to reply

EDIT: real solutions. Oops. (ignore the rest)

Your conclusion is incorrect. One example of another solution is \(\left(0,-\dfrac{1}{2}+\dfrac{\sqrt{3}}{2}i,-\dfrac{1}{2}-\dfrac{\sqrt{3}}{2}i\right)\) and permutations.

However, proving that \((1,1,1)\) is the only real solution is an easy task. From my solution, this is when \(\sqrt[3]{c+1}\) has only a real value which is only when \(c+1=0\) or \(c=-1\); then, the solution follows to be \((1,1,1)\).

Log in to reply

SOLUTION #3Similarly to solution #2, we make the polynomial \(P(x)\) and obtain \(a=-3\) and \(b=3\). However, we cannot tell what \(c\) is.

Thus, our polynomial is \(P(x)=x^3-3x^2+3x+c\) or \[P(x)=(x-1)^3+c+1\]

Solving for \(x\), we obtain \(x-1=-\sqrt[3]{c+1}\) or \[x=1-\sqrt[3]{c+1}\]

Note that there are 3 distinct values of \(\sqrt[3]{c+1}\). These three values correspond to the three solutions.

Log in to reply

The question asks for real solutions.

Log in to reply

Aww darn oops. But I can still generate the real solution by letting \(c=-1\).

Log in to reply

SOLUTION #2\[\left\{\begin{array}{l}x+y+z=3\\ x^2+y^2+z^2=3\\ x^3+y^3+z^3=3\end{array}\right.\]

Consider the polynomial \(P(x)=x^3+ax^2+bx+c\) with roots \(p,q,r\). We use newton's sums to obtain that \[p+q+r=-a\] \[p^2+q^2+r^2=a^2-2b\] \[p^3+q^3+r^3=3ab-a^3-3c\]

Now let the roots of this cubic be the variables in our equation. Thus, we have \[-a=3\] \[a^2-2b=3\] \[3ab-a^3-3c=3\]

From the first equation, we have \[\boxed{a=-3}\]

Plugging into the second equation, we have \[\boxed{b=3}\]

Plugging these into the third equation, we have \[\boxed{c=-1}\]

Thus, our polynomial \(P(x)=x^3-3x^2+3x-1\) or \[P(x)=(x-1)^3\]

Since the only roots are \(p=q=r=1\), the only solution we have for our original system of equations is \[\boxed{(x,y,z)=(1,1,1)}\]

Log in to reply

They did ask for all complex solutions and I have found \( (x,y,z) = (e^\frac{2 \pi i}{3}, e^\frac{4 \pi i}{3}, 1) \) to be a solution as well by the formula for the roots of unity. By permuting x, y and z in this solution, we also get the following solutions: \( (e^\frac{4 \pi i}{3}, e^\frac{2 \pi i}{3}, 1) \) , \( (1, e^\frac{2 \pi i}{3}, e^\frac{4 \pi i}{3}) \) , \( (1, e^\frac{4 \pi i}{3}, e^\frac{2 \pi i}{3}) \) , \( (e^\frac{2 \pi i}{3}, 1, e^\frac{4 \pi i}{3}) \) and \( (e^\frac{2 \pi i}{3}, 1, e^\frac{4 \pi i}{3}) \), which, in addition to the trivial \( (1,1,1) \) solution, leaves us with all complex solutions for the given system of equations.

Log in to reply

Simple inspection of your answer of \(\left(e^{\frac{2\pi i}{3}}, e^{\frac{4\pi i}{3}},1\right)\), we can determine that this and all of the various permutations are not solutions because they don't even satisfy \(x+y+z=3\). The only solution to problem 2 is \( (1,1,1)\).

Log in to reply

Nice I did the same thing no need to repeat

Log in to reply

SOLUTION #1Let us call the cars gas stations instead, to make the problem easier to understand.

First, let's suppose that the car has a large amount of gas initially. As it goes around the loop once, it begins and ends with the same amount of gas. In addition, there must be one gas station where the car arrives with the least amount of gas. But we're done: start at this gas station, and the car will never go lower than \(0\) gas, thus it can make it around the track once.

Log in to reply